THEORETICAL ASPECTS OF DETECTION AND MANAGEMENT OF THE CONFLICT OF INTERESTS IN BANKS OF UKRAINE - Омельчук, Ярослав; Швець, Наталія (Socio-economic relations in the digital society, 2019)
The article analyses preconditions of emergence and characteristics of conflict of interest in banks of Ukraine. A process of identifying confl ict of interest in a banking institution is described and main principles of its management are defi ned. Rules for preventing confl ict of interest by employees of banking institutions are determined. The main types of confl ict of interest emerging in the bank are defi ned and subjects of confl ict of interest cases are classifi ed. An algorithm of a management process of confl ict of interest in the bank is described in line with a model of three lines of defence.